Equity Crowdfunding dan Usaha Mikro Kecil Menengah: Kajian Equity Crowdfunding sebagai Instrumen Pendanaan UMKM Syariah: Equity Crowdfunding and Micro, Small and Medium Enterprises: Study of Equity Crowdfunding as a Sharia MSME Funding Instrument - Cici' Wilantini; Fadllan Fadllan (Islamic Economics Department, Faculty of Islamic Economics and Business, Sunan Ampel State Islamic University, Surabaya Indonesia, 2021)
Technological developments can present a financial system that is increasingly developing, effective, practical and transparent. From these developments, crowdfunding was born from a social aspect, namely helping each other and mutual cooperation that develops following technological developments. Crowdfunding is not a new concept but has been around for a long time. This article wants to study how relevant equity crowdfunding is used as a funding instrument in sharia Micro, Small and Medium Enterprises (MSMEs). This study uses library research with secondary data obtained from several books, journals, news articles, and other publications with similar research topics. Equity crowdfunding is considered relevant to be a funding system for sharia MSMEs. It is because the equity crowdfunding system does not charge interest on the part of the user of the fund, in line with sharia MSMEs that require a sharia-based funding system. This study reveals that from an Islamic perspective, equity crowdfunding is following the principles of Islamic sharia, namely avoiding MAGHRIB (maysir, gharar, haram, riba and batil); it is relevant as a funding instrument for MSMEs that produce halal products. Even so, the implementation of equity crowdfunding as a sharia MSME funding system still needs supervision from the Sharia Supervisory Board so that activities in it are monitored and do not go out of sharia principles. Keywords: Equity Crowdfunding; MSMEs; Sharia MSMEs; Funding. Abstrak: Perkembangan teknologi mampu menghadirkan sistem keuangan yang semakin berkembang, efektif, praktis dan transparansi. Dari perkembangan tersebut menjadikan crowdfunding yang lahir dari aspek sosial yaitu tolong menolong dan gotong royong ikut berkembang mengikuti arus perkembangan teknologi. Crowdfunding sebenarnya bukanlah konsep baru tetapi telah ada sejak dulu. Artikel ini ingin mengkaji bagaimana equity crowdfunding relevan digunakan sebagai instrument pendanaan dalam Usaha Mikro Kecil Menengah (UMKM) syariah. Kajian ini menggunakan penelitian kepustakaan (Library Research) dengan data skunder yang diperoleh dari beberapa buku, jurnal, artikel berita serta publikasi lainnya yang memiliki kesamaan dengan topik penelitian. Equity crowdfunding dianggap relevan menjadi sebuah sistem pendanaan bagi UMKM syariah. Hal itu disebabkan karena pada sistem equity crowdfunding tidak mengenakan bunga pada pihak pengguna dana. Senada dengan UMKM syariah yang membutuhkan sistem pendanaan berbasis syariah. Kajian ini mengungkap bahwa dari perspektif Islam, equity crowdfunding sesuai dengan prinsip-prinsip syariah Islam yaitu terhindar dari MAGHRIB (maysir, gharar, haram, riba dan batil), ia relevan sebagai instrument pendanaan UMKM yang memproduksi produk halal. Meskipun demikian, penerapan equity crowdfunding sebagai sistem pendanaan UMKM syariah tetap perlu pengawasan dari Dewan Pengawas Syariah agar aktivitas di dalamnya tetap terpantau dan tidak keluar dari prinsip-prinsip syariah. Kata Kunci: Equity Crowdfunding; UMKM; UMKM Syariah; Pendanaan.